Application of Dropshipping Method in E-Commerce to Create New Business Opportunities for Students - Putra, Dinda Syufradian; Zulfikar, Zulfikar (Knowbase : International Journal of Knowledge in Database, 2021)
This study aims to create new business opportunities for students using information technology (IT) and the internet by becoming entrepreneurs. The basic concept of using IT and the Internet is to be the main actor in the development of e-commerce and to be a part of it by using certain methods. One method that can be applied in e-commerce is the dropshipping method. With this dropshipping method, anyone can sell goods/services without having to have a stock of goods/services simply by collaborating with manufacturers, shops, and suppliers. The method in this research is an experimental research method. Explorative research aims to explore or deepen knowledge, phenomena, and new ideas to formulate problems in detail. From the research results on 32 students who became participants, the success rate of implementing the dropshipping method in this study was 71.87%, namely 23 students succeeded in selling products while nine other students failed to sell products or 28.13%. This direct practice's high level of success can be used as a reference for development and broad application in creating new business opportunities for students by becoming a dropshipper.